Risk aversion in Entrepreneurship Panels: Measurement Problems and Alternative Explanations. (1st February 2017) - Hamböck, Christian; Hopp, Christian; Keles, Cigdem; Vetschera, Rudolf
Abstract : In this study, we investigate the pitfalls associated with measuring risk aversion within studies of entrepreneurial behavior. First, we raise substantial concerns as to whether standard questions employed can be used to infer risk aversion among nascent entrepreneurs. In our work we show that the US, Canadian and Swedish panel study datasets do not offer evidence that entrepreneurs are more risk averse than non‐entrepreneurs. In fact, we show that the measurements used for risk aversion in these studies are not compatible with classic expected utility theory. Furthermore, our analysis reveals that probability weighting may even counteract the respondent's risk attitude. Therefore, inferring the respondent's risk attitude from choices in the panel study datasets can be misleading in the presence of probability weighting. We therefore suggest that alternative theories of decision making under risk, like prospect theory, are relevant and should be taken into account in future studies on entrepreneurship. Copyright © 2017 John Wiley & Sons, Ltd.